Cross-validation of distance measurements in proteins by PELDOR/DEER and single-molecule FRET - Martin F. Peter; Christian Gebhardt; Rebecca Mächtel; Gabriel G. Moya Muñoz; Janin Glaenzer; Alessandra Narducci; Gavin H. Thomas; Thorben Cordes; Gregor Hagelueken (Nature Communications, 2022)
Pulsed electron-electron double resonance spectroscopy (PELDOR/DEER) and single-molecule Förster resonance energy transfer spectroscopy (smFRET) are used to determine conformational changes and probe distances in biological macromolecules. Here the authors compare the methods on a large set of samples.